Reduction of Radiation Exposure From C-Arm Fluoroscopy During Orthopaedic Trauma Operations With Introduction of Real-Time Dosimetry. Issue 2 (February 2016) - Baumgartner, Rita; Libuit, Kiley; Ren, Dennis; Bakr, Omar; Singh, Nathan; Kandemir, Utku; Marmor, Meir Tibi; Morshed, Saam
Abstract : Objectives: The use of fluoroscopy for indirect guidance in orthopaedic trauma surgery has increased. The purpose of this investigation was to assess how real-time visualization of radiation exposure impacts dose levels during orthopaedic trauma operations. Design: Observational comparative study. Setting: Level 1 trauma center orthopaedic trauma surgery operating room. Patients/Participants: The participants in this study were 83 patients with fractures of the ankle, tibia, femur, or acetabulum receiving definitive surgical fixation of their fracture; children under 18 years of age were excluded from the study. Fellowship trained orthopaedic trauma surgeons, resident orthopaedic surgeons, radiology technicians, and scrub nurses involved in the operations on included fracture patients were also participants. Intervention: Real-time radiation exposure feedback from the Philips DoseAware device. Main Outcome Measurements: Radiation exposure from fluoroscopy compared between phase 1, during which participants were blinded to exposure levels, and phase 2, during which participants were able to see exposure levels in real time. Results: Overall mean radiation exposure was decreased by 60% in phase 2 compared with phase 1 ( P = 0.023). Mean surgeon (MS; average of primary and assistant surgeon) and mean nonsurgeon personnel (average of x-ray technician, scrub nurse, and patient) radiation exposures were decreased from phase 1 to phase 2, by 58% and 80%, respectively (MS, P = 0.034; mean nonsurgeon personnel, P = 0.043). From phase 1 to phase 2, MS radiation for femoral shaft fractures decreased by 80% or 162.0 μSv ( P = 0.02) and by 81% or 128.9 μSv ( P = 0.014) for acetabular fractures. Discussion: Our data demonstrate that real-time visualization of radiation exposure during orthopaedic trauma operations can decrease radiation exposure in the highest exposure cases. Further research is necessary to determine whether the reduction in radiation exposure is sustained over time and to understand how real-time radiation exposure data mitigates exposure. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.